Audit Keselamatan Jalan (Studi Kasus Jalan Wates Km 1 - 2, 9, Bantul Yogyakarta) - Nurkhotib (Jurusan T.Sipil Fakultas Teknik UMy, 2010)
Audit Keselamatan Jalan (Studi Kasus Jalan Wates Km 1 - 2, 9, Bantul Yogyakarta)